Rethinking sage philosophy : interdisciplinary perspectives on and beyond H. Odera Oruka - Kresse, Kai; Nyarwath, Oriare (Lanham, Maryland: Lexington books, 2023)
"This book discusses Henry Odera Oruka's sage philosophy, rethinking it in light of recent debates in African philosophy and African Studies. The chapters engage perspectives from anthropology, literature, and postcolonial scholarship, questioning and exploring the relevance of sage philosophy for current challenges, including decolonialization"--
Includes bibliographical references and index.
Keywords: Oruka, H. Odera; Philosophers -- Kenya -- Biography; Philosophy -- Africa, Sub-Saharan.; Philosophy, African